Síntese e arranjos supramoleculares de complexos Bis(triazenido) macrocíclicos e triazenido 1-óxido com os cátions Cu2+, Ni2+, Cu+, K+ - Santos, Aline Joana Rolina Wohlmuth Alves dos (2010)
This work elaborates on the determination of crystal and molecular structures of four pro-ligands, emphasizing bis(triazenes), triazene 1-oxide and a new class of bis(triazenes) macrocyclic, and eight complexes involving Cu+, Cu2 +, Ni2 + and K+. Pro-ligands triazenes 1-oxide are relatively small and simple molecules. When they are deprotonated they presen a high ability to form supramolecular assemblies, either because they are planar and facilitate the metal-metal approach and the formation of π···π interactions _ as in the case of complex (2) _, or because they have substituents with capacity of act as agent of secondary complexation forming polycationic structures _ as in the case of complex (3). Pro-ligand bis(triazenes) are double agents of complexation. The bis(triazene) (4) complexed Copper(I) forming a binuclear complex (5). The same ligand also led to binuclear complexes of Copper(II) through the chelate and macrocyclic effect, forming two types of crystal structures, one non-centrosymmetric (6), the other centrosymmetric (7). The pro-ligand bis(triazene) macrocyclic (8) has a cavity with ideal size for the complexation of transition metals, resulting, for example, in complex (9) with the cation Nickel(II). The ligand in this complex has substituents in para position. These substituents, two pyridine molecules (in the coordination sphere of the metal) and two pyridine molecules (as solvate of crystallization) form weak electrostatic interactions in the supramolecular arrangement. The bis(triazene) macrocyclic (10) has a central cavity larger than the bis(triazene) macrocyclic (8), allowing the complexation of larger molecules or ions. The analysis by X-ray diffraction on single crystal for the compound (10) revealed the presence of disordered water molecules inside the cavity, forming a chain of water molecules perpendicular to the stacked molecules of (10). When the compound (10) is deprotonated with a weak base such as pyridine, the deprotonation occurs partially, leading to a binuclear complex with Copper(II)-bridged μ2-OH (11). Two molecules of the ligand coordinate the two Copper(II) cations, and the coordination sphere is completed by two axial pyridine molecules. When the compound (10) is deprotonated with a strong base such as sodium or potassium ethanolate, the deprotonation occurs totally, leading to a binuclear conmplex with Copper(II)-bridged μ2-OCH2CH3 (12). One molecule ligand coordinates two Copper(II) cations and the coordination sphere is also supplemented by two axial pyridine molecules. The synthesis of a new class of macrocyclic triazenes has been successfully performed as well as the synthesis of their metallic complexes. The characterization of their structures and supramolecular assemblies was performed using the analysis by X-ray diffraction on single crystal and other secondary methods.